Sudden Cardiac Arrest Survivorship: A Scientific Statement From the American Heart Association - Sawyer, Kelly N; Camp-Rogers, Teresa R; Kotini-Shah, Pavitra; Del Rios, Marina; Gossip, Michelle R; Moitra, Vivek K; Haywood, Kirstie L; Dougherty, Cynthia M; Lubitz, Steven A; Rabinstein, Alejandro A; Rittenberger, Jon C; Callaway, Clifton W; et al. (Circulation (New York, N.Y.), 2020)
Cardiac arrest systems of care are successfully coordinating community, emergency medical services, and hospital efforts to improve the process of care for patients who have had a cardiac arrest. As a result, the number of people surviving sudden cardiac arrest is increasing. However, physical, cognitive, and emotional effects of surviving cardiac arrest may linger for months or years. Systematic recommendations stop short of addressing partnerships needed to care for patients and caregivers after medical stabilization. This document expands the cardiac arrest resuscitation system of care to include patients, caregivers, and rehabilitative healthcare partnerships, which are central to cardiac arrest survivorship.